APLIKASI VISUALISASI PADA SISTEM MODEL LIFT - Andri Sukmaindrayana (LPPM STMIK DCI, 2014)
Lifts are widely used in supermarkets life, apartments, high rise buildings and buildings other high floored. The elevator is already circulating using simple logic language there is controlled manually by humans, some already are using microcontroller, and an algorithm searching algorithm and other controls that use different programming languages. And produce good products also have a high degree of precision where the error of the human factor can be minimized. Control the use of several searching algorithms.To run the elevators most widely used is the use of PLC (Programmeble Logic Controller) because it's easier to control the lift and also more durable because it's a lot of people are getting interested and studying the elevator control system. As the development of the role of the computer era increasingly dominated life. Moreover, today's computers are expected to be used to do everything that can be done by either man in the household, even in the education industry. To solve the problem with the computer, the program must be made in advance and then be processed further. Without the program, the computer is just a metal box that is not useful.Keyword : Lifts, Programmeble Logic Controller, Searching Algorithms.